(untitled) (Our Nature, 2017)
The present paper attempts to report a total of 118 fish species spread over 11 orders, 26 families and 64 genera inhabited indifferent water bodies viz, rivers, reservoirs, streams, ponds, lakes, canals, ditches, paddy fields of Morang district, collected during a one-year survey. The order Cypriniformes is the richest one among 11 orders that comprises 59 species followed by Siluriformes having 31 and Perciformes with 19 representatives, respectively. Orders Anguilliformes, Osteoglossiformes, Beloniformes, Cyprinodontiformes, Synbranchiformes and Tetraodontiformes have only one representative. Olyra longicaudata is the new report from Morang district and the second report from Nepal. Besides this, other hill-stream fishes viz., Pseudecheneis sulcatus, Schizothorax plagiostomus, Schistura savona and Neolissochilus hexagonolepis recorded during the survey, also have not been previously reported from this district.